2020
DOI: 10.3389/fcimb.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis PE31 (Rv3477) Attenuates Host Cell Apoptosis and Promotes Recombinant M. smegmatis Intracellular Survival via Up-regulating GTPase Guanylate Binding Protein-1

Abstract: The Mycobacterium (M.) tuberculosis comprising proline-glutamic acid (PE) subfamily proteins associate with virulence, pathogenesis, and host-immune modulations. While the functions of most of this family members are not yet explored. Here, we explore the functions of "PE only" subfamily member PE31 (Rv3477) in virulence and host-pathogen interactions. We have expressed the M. tuberculosis PE31 in non-pathogenic Mycobacterium smegmatis strain (Ms_PE31) and demonstrated that PE31 significantly altered the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…It has been reported that Mycobacterium tuberculosis inhibits caspase-3 leading to a reduction in macrophages apoptosis (Ali et al, 2020). Increased level of CD4+CD25+FOXP3+ T regulatory cells has been reported in Crohn's disease and intestinal tuberculosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Mycobacterium tuberculosis inhibits caspase-3 leading to a reduction in macrophages apoptosis (Ali et al, 2020). Increased level of CD4+CD25+FOXP3+ T regulatory cells has been reported in Crohn's disease and intestinal tuberculosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, PE_PGRS62 ( Long et al, 2019 ) and PE_PGRS18 ( Yang W. et al, 2017 ) can decrease apoptosis and enhance survival rate. PE31 increased guanylate-binding protein-1 (GBP-1) expression and inhibited caspase-3 activation and macrophage apoptosis through the NF-κB pathway ( Ali et al, 2020 ). Although apoptosis caused by some bacterial proteins favors bacterial survival, it also helps to kill intracellular bacteria and activate adaptive immunity ( Schaible et al, 2003 ; Srinivasan et al, 2014 ).…”
Section: Role Of Pe/ppe Proteins In Host–pathogen Interactionsmentioning
confidence: 99%
“…Multiple cellular processes, including phagocytosis, autophagy, apoptosis, and inflammasome formation, have been adopted by alveolar macrophages to resist the invading Mtb ( Shim et al., 2020 ). Mtb also displays an extraordinary ability to evade components of the innate immunity and successfully inhabit the host through long-term evolution ( Liu et al., 2017 ), which could be partially attributed to the abundance of virulence factors released by Mtb ( Zhang et al., 2018 ; Qiang et al., 2019 ; Ali et al., 2020 ). Rv0790c is predicted to be a 27 kDa conserved hypothetical protein of Mtb , with studies indicating that Rv0790c expression is elevated in Mtb -infected macrophages, and that it correlates with moyR, a potential monooxygenase regulator ( Parvati Sai Arun et al., 2018 ; Abeywickrama and Perera, 2021 ).…”
Section: Discussionmentioning
confidence: 99%